REPRESENTATION OF UNDERAGE SEX IN THE FILM “DUA GARIS BIRU” DIRECTED BY GINATRI S. NOER - Mohammad Rafi Mustaqim; Reindy Aziqar Pasya; Marudut Bernadtua Simanjuntak (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2022)
The film "Dua Garis Biru" is a film that is popular in Indonesian society and impresses people because it creates controversy in its scenes. Bima and Dara are a teenage couple as the main characters of the film who have carried out activities beyond their limits as teenagers. The purpose of this study is to find out the description of teenage couples who have sex outside of marriage and face big problems involving Dara being pregnant and they must be responsible for what they experience with lots of opposition from the family, social background, and different ideologies. At first, they did not want to tell their parents about their condition because they were undergoing high school education. However, during school activities, Dara experienced pain and called her parents. From here, the peak of the problem occurred because of a dispute between the Bima family and Dara's family. This film educates young people about love, friendship, and family relationships in today's world. The film also teaches parents about sexual education, which sometimes parents are embarrassed to talk about with their children. The research was conducted using qualitative methods and content analysis techniques.